Children Comorbidities Associated with High Parental Self-Efficacy: A Study on Parents of Children with Down Syndrome - Candra, Fitriyani Mutiara; Utari, Agustini; Winarni, Tri Indah (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Parental self-efficacy (PSE) in parents of children with Down syndrome (DS) refers to parents’ efficacy in their capability as parents nurturing their children with DS. Therefore, this study aimed to determine factors that may influence PSE in parents of children with DS. Methods: This cross-sectional study was carried out on 87 parents of children with DS. Self-Efficacy Parenting Task Index (SEPTI) was administered to measure PSE levels. Spearman’s rank correlation and independent t-test were applied to determine factors that may influence PSE. These include gender, children’s age, duration of being diagnosed with DS, comorbidities, number of children in the family, parents’ age, educational level, monthly household income, place of residence, genetic counseling, and support group. Results: The results showed that the median scores of SEPTI were 114 (101-143), and 57.5% of parents had moderate PSE levels. Significant factors affecting PSE include children with comorbidities (r = - 0.197, p = 0.033) and the place of residence (r = -0.212, p = 0.024). Parents of children with fewer comorbidities (119 (109-128), p =0.034), those with higher education (118 (110-132), p = 0.031), and those living in urban areas (115 (101-143), p = 0.025) demonstrated higher PSE. Additionally, multiple linear regression analysis showed children’s comorbidity as the most significant predictor in PSE (PR= 0.17, 95% CI = 0.03 - 0.77, p = 0.020). Conclusions: Children with comorbidities affect self-efficacy in parents of children with DS, besides the level of parent’s education and the place of living identity.